The influence of GAP‐43 on orientation of cell division through G proteins. Issue 47 (14th September 2015) - Huang, Rui; Zhao, Junpeng; Ju, Lili; Wen, Yujun; Xu, Qunyuan
Abstract: Recent studies have shown that GAP‐43 is highly expressed in horizontally dividing neural progenitor cells, and G protein complex are required for proper mitotic‐spindle orientation of those progenitors in the mammalian developing cortex. In order to verify the hypothesis that GAP‐43 may influence the orientation of cell division through interacting with G proteins during neurogenesis, the GAP‐43 RNA from adult C57 mouse was cloned into the pEGFP‐N1 vector, which was then transfected into Madin–Darby Canine Kidney (MDCK) cells cultured in a three‐dimensional (3D) cell culture system. The interaction of GAP‐43 with Gαi was detected by co‐immunoprecipitation (co‐IP), while cystogenesis of 3D morphogenesis of MDCK cells and expression of GAP‐43 and Gαi were determined by immunofluorescence and Western blotting. The results showed are as follows: After being transfected by pEGFP‐N1‐GAP‐43, GAP‐43 was localized on the cell membrane and co‐localized with Gαi, and this dramatically induced a defective cystogenesis in 3D morphogenesis of MDCK cells. The functional interaction between GAP‐43 and Gαi proteins was proven by the co‐IP assay. It can be considered from the results that the GAP‐43 is involved in the orientation of cell division by interacting with Gαi and this should be an important mechanism for neurogenesis in the mammalian brain.